SISTEM PAKAR MENDETEKSI PENYAKIT PADA TANAMAN SAYUR SAWI DENGAN METODE BAYES - Friska Nainggolan; , Harvei Desman Hutahaean; Asaziduhu Gea (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Mustard vegetables are classified as leaf vegetables from the Cruciferaefamily which have high economic value and are very popular among the people. Mustard vegetables are often used by people as processed ingredients in various types of cuisine. In general, Vegetable Vegetables are planted in the lowlands to the highlands and harvest is done at the age of 30 - 60 days after planting, depending on the variety. Expert systems are systems that try to adopt human knowledge to computers, so that computers can solve problems as usual by experts. Bayes method is one of the methods found in expert systems that can calculate or process the probability values of each symptom. The expert system detects mustard plant disease has 5 types of diseases found in mustard vegetable plants, namely seedlings, leaf rot, clubroot, leaf spot, alternaria rot.